Effects of aerobic exercises on physical fitness of primary school children - Manh Nguyen, Hung; Nguyen, Luc Tri (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The effects of aerobic exercises on physical fitness in school children have not yet been examined in the context of Vietnam. The aim of this study was to verify the effects of aerobic exercises on physical fitness of primary school children. This study was a controlled trial involving 64 third-grade primary school children, all aged 8 years, from Vinh City, Vietnam. Participants voluntarily took part and were randomly assigned to either the aerobic exercise group (AG) or the control group (CG), with 32 children in each group (16 males and 16 females per group). Five physical fitness tests were conducted: handgrip strength (upper-body strength), 30-second sit-ups (abdominal endurance), standing long jump (leg power), 30-meter sprint (speed), and 4×10 m shuttle run (agility). After eight weeks of intervention, the aerobic exercise group (AG) showed significantly greater improvements than the control group (CG) in upper- and lower-extremity strength, abdominal strength, speed, body control, and endurance (p < 0.05). These findings suggest that aerobic exercise effectively enhances muscular strength, speed, agility, and overall endurance in primary school children.